If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x-5+5=2x-12
We move all terms to the left:
x-5+5-(2x-12)=0
We add all the numbers together, and all the variables
x-(2x-12)=0
We get rid of parentheses
x-2x+12=0
We add all the numbers together, and all the variables
-1x+12=0
We move all terms containing x to the left, all other terms to the right
-x=-12
x=-12/-1
x=+12
| 6t+13=19t-8 | | 50-2x=40-1.50 | | X+x=27.5 | | 11+20w=25w-14 | | 5x+6=3.6+7x | | 27+0.35p=76 | | 45+5x=12.50 | | -45+2x=x+23 | | Y=-x2+25 | | 5p(-2)-2p+21=-1 | | 3x^2−12x+20=0 | | 14=21-7y | | 4n+3=2(2n+1)+1 | | 6x=983 | | 7.2=2n-4 | | -3=4h | | 1/(6x^2)=1/(3x^2)-1/x | | W+z=5 | | Y=2x+5x+2 | | −8+(x/7)=−10 | | 2/3t+1/4=3/4t+1/6 | | -3y+5=2y+4 | | 5.4=2.3-07y | | 5=7x+26+2x–12x | | x*9=19 | | 15+0.50m+2=25+0.25m | | x*6=19 | | -45+2x+2x=x+23 | | 39+2x=x+27 | | (n)9=44 | | 4x+6-8x-2=3+1 | | F(x)=12-3/4x |